Sensory Elements and Devices Operational Diagnostic Blood Glucose Using Near Infrared Radiation - Kotyk, M. V.; Kogut, I. T.; Saffouri, Ch. G. (Physics and Chemistry of Solid State, 2017)
The article describes a method for measuring the concentration of glucose in human blood by the non-invasive methods using near-infrared optical technology. In medical practice, glucose concentration in the blood in most cases is measured by invasive methods involving the collection of blood from the finger or vein, while non-invasive devices for determining the level of glucose preserve the operational measurement of blood-borne levels. Invasive methods are expensive and painful. Frequent piercing of fingers causes corns on the skin, and also increases the risk of spreading infectious diseases. Thus, the development of a system of non-invasive measurement of glucose in the blood will be useful for patients with diabetes mellitus. The proposed system consists of emitters of signals with a wavelength of 940 nm. These optical signals are sent through the earlobe, and the rays passing through it are fixed by a phototransistor located on another part of the device. The concentration of glucose in the blood is determined by analyzing the intensity variation obtained after passing the signal. The accuracy of the measurements of the proposed system can be improved by integrating its sensitive and emitting elements based on the SOI of the CMOS structures.